2015
DOI: 10.9758/cpn.2015.13.1.103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cognitive Decline and Psychopathology in Patients with Schizophrenia and Bipolar Disorder

Abstract: ObjectiveThe primary goals of the present study were to assess intellectual function in participants with schizophrenia or bipolar disorder (BD) and to investigate the relationships between cognitive decline and the severity of each type of psychopathology.MethodsThe present study included 51 patients with schizophrenia and 42 with BD who were recruited from the psychiatry outpatient clinic of Jeju University Hospital between March 2011 and March 2014. The Korean Wechsler Adult Intelligence Scale (K-WAIS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Currently, the dimensional approach for diagnosing mental disorders has revitalized the question of shared characterization of SCZ and BD in a dimensional continuum view, as opposed to a categorical dichotomous vision. This has been supported by the neurobiological research that has shown that SCZ and BD exhibit shared genetic [ 4 , 5 ] and neurocognitive determinants [ 6 ], besides clinical features [ 7 ]. The investigation of the neuroanatomical characteristics of the two disorders can therefore help to further delineate their common and different pathophysiological bases, opening the door to the development of tailored instruments with higher diagnostic specificity.…”
Section: Introductionmentioning
confidence: 94%
“…Currently, the dimensional approach for diagnosing mental disorders has revitalized the question of shared characterization of SCZ and BD in a dimensional continuum view, as opposed to a categorical dichotomous vision. This has been supported by the neurobiological research that has shown that SCZ and BD exhibit shared genetic [ 4 , 5 ] and neurocognitive determinants [ 6 ], besides clinical features [ 7 ]. The investigation of the neuroanatomical characteristics of the two disorders can therefore help to further delineate their common and different pathophysiological bases, opening the door to the development of tailored instruments with higher diagnostic specificity.…”
Section: Introductionmentioning
confidence: 94%
“… 37) Accompanying these phenomena are cognitive deterioration and functional decline in such areas as occupation, social relationships, and financial independence with eventual loss of autonomy. 38) Research efforts in the last few decades have started to uncover the neurobiological correlates of the worsening clinical course in BD. The term “neuroprogression” has been increasingly used to define the pathological reorganization of the central nervous system (CNS) which arises as the result of several insults, such as inflammation and oxidative stress.…”
Section: Main Subjectsmentioning
confidence: 99%
“…The included measures are all putative endophenotypes for psychosis and were compatible across centers, thus reaching substantial sample sizes: P300 event‐related potential: reduced amplitude and prolonged latency of the P300 wave have consistently been found in patients with psychotic illnesses as well as in their unaffected relatives, compared to controls (Bestelmeyer, Phillips, Crombie, Benson, & St.Clair, ; Blackwood, St Clair, Muir, & Duffy, ; Bramon et al, ; Díez et al, ; Mondragón‐Maya et al, ; Pierson, Jouvent, Quintin, Perez‐Diaz, & Leboyer, ; Price et al, ; Schulze et al, ; Turetsky et al, ; Weisbrod, Hill, Niethammer, & Sauer, ; Winterer et al, ). The P300 is thought to be a correlate of attention and working memory (Ford, ; Näätänen, ). Cognitive performance: deficits on cognitive tests such as digit span (measuring working memory), block design (measuring working memory and spatial visualization), and the Rey Auditory Verbal Learning Task (RAVLT) immediate and delayed recall (measuring short and long term verbal memory, respectively) are common and persistent across psychotic disorders (Bora, Yucel, & Pantelis, ; Bora & Pantelis, ; Gur et al, ; Heinrichs & Zakzanis, ; Kim et al, ; Lee et al, ). Abnormalities are often observed before the onset of the illness as well as in unaffected relatives (Birkett et al, ; Forbes, Carrick, McIntosh, & Lawrie, ; Glahn et al, ; Ivleva et al, ; Park & Gooding, ; Reichenberg et al, ; Saperstein et al, ; Snitz, Macdonald, & Carter, ). Lateral ventricular volume: increased ventricular volume is a highly replicated finding in patients with psychosis compared to controls (Boos, Aleman, Cahn, Hulshoff Pol, & Kahn, ; Crespo‐Facorro et al, ; Fannon et al, ; Fusar‐Poli et al, ; Haijma et al, ; Kempton, Stahl, Williams, & DeLisi, ; Kumra et al, ; McDonald et al, , ; Sharma et al, ; Shenton, Dickey, Frumin, & McCarley, ; Strasser et al, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%